(untitled) (Marketing Journal, 2026)
Abstract The article examined the environmental taxation system and its economic effectiveness in the European Union member states. Arthur Pigou’s theory of externalities and Lawrence Goulder’s double dividend hypothesis were applied as the theoretical framework. Statistical information from Eurostat and the World Bank was used to analyse the structure of environmental tax revenues, their role in the economy, and the distribution across tax categories. The findings indicated that environmental taxes contributed to emission reduction without generating negative effects on economic development. Sweden’s carbon tax experience demonstrated that the implementation of carbon pricing improved environmental indicators while maintaining stable economic growth. The study showed that the gradual introduction of environmental taxes and effective revenue recycling generated positive economic and environmental outcomes. Keywords: environmental tax, carbon pricing, double dividend, Pigouvian tax, green fiscal reform, emissions trading system.